Rasio biomasa dan kelimpahan makrozoobenthos sebagai penduga tingkat pencemaran di teluk jakarta - . Yonvitner; Zulhamsyah Imran (Institut Pertanian Bogor, 2006)
The monitoring technic using aquatic organism as bio indicator was more advance. Monitoring of water quality conduct with biological indicator among macrobentic biomass and green mussel population were intensively used by researcher. These research was consider that water quality damage on Jakarta bay might be identity with biomass analysis approach. Benthic organism used as sample were macrozoobenthos and green mussel (Pema viridis). Water quality was analysed using Fsawb (Fish and Wild Life Method) index from ott. 1979, then for biomass model was analysed by dominant cumulative curve. Result of this research showed that Fsawl index average was 64.99, that its value was unappropriate for fishes. The analysis of abundance and biomass comparison index was tend to increase the density, while the biomass was decrease. The results indicate that water body was already polluted. The si:: nificant impact for mussel of pollution was appear on water column at 2 m under of sea level.